Analisis Pengaruh Kualitas Website E-Learning Ujian Online SMK Pelayaran Ampari Jayapura - natalia betty ansanay (CV Edujavare Publishing, 2025)
The purpose of this study was to evaluate the level of end user satisfaction with the e-learning website at SMK Pelayaran Ampari using the End User Computing Satisfaction (EUCS) approach. The EUCS method includes five main variables, namely content, accuracy, format, ease of use, and timeliness. Data collection was carried out by distributing questionnaires to 60 respondents who were active students who had used the website. The results of data processing showed that the average score for each variable was: content 3.97; accuracy 3.88; format 3.85; ease of use 3.90; and timeliness 3.83. Of the five variables, the content variable had the highest score, indicating that the information presented in the system was considered relevant and according to user needs. However, the timeliness variable got the lowest score, indicating that the speed and timeliness of the system in presenting information or exam access still needed to be improved. Overall, the average score of 3.89 indicated that users were quite satisfied with the available system. Recommendations for improvement are directed at improving system performance in terms of access speed, exam time management, and interface features to be more interactive and responsive. It is hoped that the results of this study can be a reference for developers and system managers in improving the quality of e-learning services during exam implementation.